An evidence map of randomised controlled trials evaluating genetic therapies. Issue 4 (10th November 2020) - Apaydin, Eric A.; Richardson, Andrea S.; Baxi, Sangita; Vockley, Jerry; Akinniranye, Olamigoke; Ross, Rachel; Larkin, Jody; Motala, Aneesa; Azhar, Gulrez; Hempel, Susanne
Abstract : Objectives: Genetic therapies replace or inactivate disease-causing genes or introduce new or modified genes. These therapies have the potential to cure in a single application rather than treating symptoms through repeated administrations. This evidence map provides a broad overview of the genetic therapies that have been evaluated in randomised controlled trials (RCTs) for efficacy and safety. Eligibility criteria: Two independent reviewers screened publications using predetermined eligibility criteria. Study details and data on safety and efficacy were abstracted from included trials. Results were visualised in an evidence map. Information sources: We searched PubMed, EMBASE, Web of Science, ClinicalTrials.gov and grey literature to November 2018. Risk of bias: Only RCTs were included in this review to reduce the risk of selection bias in the evaluation of genetic therapy safety and efficacy. Included studies: We identified 119 RCTs evaluating genetic therapies for a variety of clinical conditions. Synthesis of results: On average, samples included 107 participants (range: 1–1022), and were followed for 15 months (range: 0–124). Interventions using adenoviruses (40%) to treat cardiovascular diseases (29%) were the most common. Description of the effect: In RCTs reporting safety and efficacy outcomes, in the majority (60%) genetic therapies were associated with improved symptoms but in nearly half (45%) serious adverse event (SAEs) were also reported. Improvement was reported in trials treating cancer, cardiovascular, ocular and muscular diseases. However, only 19 trials reported symptom improvement for at least 1 year. Strengths and limitations of evidence: This is the first comprehensive evidence map of RCTs evaluating the safety and efficacy of genetic therapies. Evidence for long-term effectiveness and safety is still sparse. This lack of evidence has implications for the use, ethics, pricing and logistics of genetic therapies. Interpretation: This evidence map provides a broad overview of research studies that allow strong evidence statements regarding the safety and efficacy of genetic therapies. Most interventions improve symptoms, but SAE are also common. More research is needed to evaluate genetic therapies with regard to the potential to cure diseases.